2016
DOI: 10.1002/jsfa.8043
|View full text |Cite
|
Sign up to set email alerts
|

Removal of six pesticide residues in cowpea with alkaline electrolysed water

Abstract: This study demonstrated that AlEW solution with pH of 12.2 could be used to reduce pesticide residues on fresh cowpea samples. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Electrolyzed oxidizing (EO) water is extensively used with a low pH and high oxidation–reduction potential. Electrolyzed reduced (ER) water has limited application due to its characteristic of a high pH and low ORP [10,11]. However, researchers found that the ER water could be used as a cleaning solution to reduce pesticide residues in fruits and vegetables; for example, cabbage, leek [2], beans, grapes [3], and cowpea [11].…”
Section: Introductionmentioning
confidence: 99%
“…Electrolyzed oxidizing (EO) water is extensively used with a low pH and high oxidation–reduction potential. Electrolyzed reduced (ER) water has limited application due to its characteristic of a high pH and low ORP [10,11]. However, researchers found that the ER water could be used as a cleaning solution to reduce pesticide residues in fruits and vegetables; for example, cabbage, leek [2], beans, grapes [3], and cowpea [11].…”
Section: Introductionmentioning
confidence: 99%
“…A 1 μL sample was injected in the splitless mode, with a splitless time of 1.0 min and a split flow of 50 mL min −1 . Selected ion monitoring (SIM) mode was performed . Each analysis was repeated for three times.…”
Section: Methodsmentioning
confidence: 99%
“…The treated samples were air-dried. 23 Pesticide residues extraction and purification procedure A 5 g amount of per homogenised sample was put into a 50 mL centrifuge tube and 40 mL of acetonitrile was added, and then shaken for 30 min. Then, 4 g of anhydrous MgSO 4 and 1 g of NaCl were added to the tube, and the mixture was shaken for 30 min and centrifuged for 5 min at 3100 g, after which 10 mL of supernatant was removed into a test tube and concentrated to 2 mL by using a N-EVAP 112 nitrogen-evaporator (Organomation, Berlin, MA, USA).…”
Section: Pesticide Residue Removal Effect Of the Css Detergent Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Pesticides remain in end products such as fruit or juice . Due to their carcinogenic, toxic, and mutagenic effects, pesticide residues have become a major health concern with important economic consequences …”
Section: Introductionmentioning
confidence: 99%